ANALISIS MANFAAT LANGSUNG SUMBERDAYA MANGROVE PADA KAWASAN EKOWISATA MANGROVE LANTEBUNG KOTA MAKASSAR - Nurdin Nurdin; Nur Ifra Khumaera; Yukiki Hiro Mantu (Universitas Pattimura, 2021)
The mangrove ecosystem has a significant role in economic, social and security activities for the surrounding community. Mangrove resources have great direct benefits if the sustainability of their biological resources is maintained. This study examines the value of direct benefits of mangrove resources in the Lantebung mangrove ecotourism area, Makassar City. This study uses primary data derived from interviews with respondents in the Lantebung ecotourism area and secondary data derived from scientific literature studies. Respondents were selected using purposive sampling method. Based on the results of the study, it was identified that the direct benefits in the Lantebung mangrove ecotourism area were the value of tourism benefits, trade benefits and fishery benefits. Based on the results of the study, it was found that the direct benefit value of mangrove resources in the Lantebung Ecotourism area was Rp 2,387,400,000-/year, which detailed the value of tourism, which was Rp 167.400.000/year, the value of trade was Rp 381.600.000/year and the value of fisheries was Rp 1.838. 400.000/year.